KORELASI DURASI TIDUR DAN KUALITAS TIDUR DENGAN KEJADIAN HIPERTENSI PADA USIA PRODUKTIF - Hamzah, Hamzah; Lestari, Dwi; Hermansyah, Hermansyah; Sendra, Eny (Ensiklopedia of Journal, 2025)
Hypertension is a medical condition characterized by a persistent increase in arterial blood pressure, where systolic pressure reaches or exceeds 140 mmHg and diastolic pressure reaches or exceeds 90 mmHg. The purpose of this study was to determine the correlation between sleep duration and sleep quality with the incidence of hypertension in productive age. The research design used in this study was cross-sectional. The study was conducted in the Tanakeke Community Health Center Working Area. The study was conducted in December 2024. The population consisted of all patients who came to the health center and were of productive age. The sample consisted of 45 people. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between sleep duration (p-value: 0.04) and sleep quality (pvalue: 0.00) with the incidence of hypertension in the productive age group. It is recommended that respondents improve their sleep patterns, both in terms of duration and quality, to maintain blood pressure. Keywords: Sleep Duration, Hypertension, Sleep Quality.